Ballistic kiss - Kadrey, Richard (Kadrey, Richard. Sandman Slim novel, 2021)
"As the battle between warring angels continues, James Stark is focused on seemingly simpler matters now that he's resurfaced on earth: an invasion of ghosts. L.A.'s Little Cairo neighborhood has suddenly been overrun by violent spirits, and Thomas Abbott knows if anyone can figure out why they've appeared--and how to get rid of them--it's Stark. Armed with the Room of Thirteen Doors, Stark quickly learns that the answer may reach back to the 1970s and the unsolved murder of small-time actor, Chris Stein. As he begins to dig into the cold case, another area of Stark's life takes an unexpected turn when he becomes entangled with Janet, a woman he saved during the High Plains Drifter zombie attack. Janet's brush with the living dead hasn't quenched her thirst for danger. She's an adrenaline junkie and a member of The Zero Lodge--a club that promises "there's zero chance you'll get out alive." After Stark joins the Lodge to be with Janet, he makes a pair of crucial discoveries that could decide the fate of LA and Heaven itself. To prevent the Little Cairo haunting from consuming the city, Stark must piece together the connections between the Lodge and a missing angel. But while he may dispatch the ghosts, Stark knows that without his help, the bloody war in Heaven could rage forever."--Back cover.